A systematic review and meta-analysis of effects of spironolactone on blood pressure, glucose, lipids, renal function, fibrosis and inflammation in patients with hypertension and diabetes. (4th May 2021) - Lin, Mengyue; Heizati, Mulalibike; Wang, Lin; Nurula, Muyesaier; Yang, Zhikang; Wang, Zhongrong; Abudoyreyimu, Reyila; Wu, Zihao; Li, Nanfang
Abstract: Purpose: Hypertension commonly co-exists with diabetes mellitus (DM), and both are closely related to adverse health outcomes. The activation of aldosterone and mineralocorticoid receptor (MR) may play important roles in this process. Therefore, we aim to evaluate the efficacy of MR antagonists on cardiovascular risk factors, including blood pressure (BP), glucose, lipids, renal function, fibrosis and inflammatory and its safety in patients with both hypertension and DM. Methods: We searched PubMed, Embase, Web of Science and Cochrane databases for clinical trials published until December 31, 2019. Studies comparing the effect of spironolactone to placebo in patients with hypertension and DM were included. Mean difference with 95% confidence intervals was used to report outcomes. Results: Eleven randomised placebo-controlled trials with 640 participants were finally included with mean follow-up of 5 months. Compared to placebo, spironolactone significantly reduced office systolic (–6.57, 95%CI: −9.21, −3.93) and diastolic BP (–2.63, 95%CI: −4.25, −1.02) as well as ambulatory BP; increased glycosylated haemoglobin by 0.3 but no clear effect on fasting glucose. Spironolactone induced a significantly reduction of urinary albumin but increased serum creatinine (7.60, 95%CI: 4.94, 10.27) and decreased glomerular filtration rate (–4.28, 95%CI: −6.38, −2.18). Markers of fibrosis and inflammation, including NIIINP, PICP, hs-CRP and TNF-α were also decreased after spironolactone therapy. For lipid metabolism, there was no significant difference between groups. Spironolactone mildly increased serum potassium (0.30, 95%CI: 0.23, 0.37). 2.5% subjects treated with spironolactone experienced mild to moderate hyperkalaemia and received medication or dietary advice and another 1.6% developed severe hyperkalaemia and withdrawn from the studies. Conclusion: Spironolactone reduced BP and urinary albumin, improve fibrosis and inflammation, whereas slightly increases the glycosylated haemoglobin and serum creatinine in patients with hypertension and diabetes. Long-term RCTs to assess the effects of spironolactone on cardiovascular events in this population are warranted.